The Role of Digital Transformation in the Implementation of Management Accounting Systems at PT Kawasan Industri Makassar (KIMA) - Juanda Astuti; Chairul Ihsan Burhanuddin; Muttiarni Muttiarni (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Digital transformation has become a strategic necessity for organizations seeking to improve information quality, operational efficiency, and managerial decision-making. In industrial estate management companies, the complexity of operational activities requires an integrated information system capable of providing accurate and timely data. Despite the widespread adoption of Enterprise Resource Planning (ERP) systems, empirical evidence regarding their role in supporting management accounting systems within industrial estate organizations remains limited. This research explores the implementation of an SAP-based ERP system as part of digital transformation at PT Kawasan Industri Makassar (KIMA) and examines its contribution to management accounting practices and managerial decision-making. A qualitative descriptive approach was employed through interviews, observations, and documentation involving key personnel directly engaged in system utilization. The analysis reveals that ERP implementation has enhanced the quality of management accounting information by improving data integration, reporting structure, information accuracy, and transaction traceability. The system supports key management accounting functions, including costing, budgeting, and performance measurement, while facilitating more structured monitoring and evaluation processes. From the perspective of technology acceptance, users recognize the usefulness of the system in managing organizational data, although challenges related to adaptation and data-entry consistency remain evident. These findings highlight the practical contribution of ERP-driven digital transformation in strengthening management accounting systems while emphasizing the importance of human resource readiness and continuous system optimization to maximize organizational benefits.